Adam of the road - Vining, Elizabeth Gray, 1902-1999.; Lawson, Robert, 1892-1957 (New York, The Viking Press, 1942)
In thirteenth-century England an eleven-year-old boy roams the countryside as he searches for his father and his stolen dog.
G9
Keywords: Middle Ages -- Fiction; Great Britain -- History -- Plantagenets, 1154-1399 -- Fiction